Analisis Bibliometrik Terhadap Online Marketing - Setyoningsih, Sari (STIE PENA, 2023)
The technological of the internet has increased the demand for online marketing strategies. Over the years, online marketing has received a lot of attention because of the benefits for both personal and organizational. This study attempts to analyze online marketing from 2018 to 2022 through a bibliometric analysis procedure. A total of 200 articles were published retrieved from the Google Scholar database for analysis. The purpose of this study is to analyze developments research related to online marketing that will be useful later for recommendations for further research. This study uses a quantitative method take advantage of Publish or Perish software, Google Scholar, VOSViewer and Mendeley. This research is conducted to see how the consumers’ brand perception and purchasing decisions are influenced by different online marketing tools used such as components of online marketing. This is one of the pioneering studies which provides a greater explanation of online marketing research by investigating its evolution through bibliometric analysis.Keywords: Bibliometric Analysis; E-Commerce; Online Marketing; Social media